Analisis Produktivitas Produksi Roti Sisir di Best Dough Bakery Malang - Ahana, Gloria Irene Rambu; Budiharti, Nelly; Myrtanti, Reiny Ditta (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Best Dough Bakery is a bread business that produces comb bread as its main and superior product. However, there is a problem encountered, where there is a deviation between the production results and the predetermined production target. This indicates a problem in production productivity so it is necessary to measure productivity. The methods used in this research are objective matrix (OMAX) and fishbone diagram. The results obtained from the highest productivity value occurred in July which was 501.25 while the lowest productivity occurred in April which was 352. The highest score is in criterion 5, which is the comparison between total machine downtime and machine usage time with a total score of 43. While the lowest score is in criterion 2, which is the comparison between production results and employee working hours with a score of 29. Therefore, criterion 2 is the priority for improvement as well as the main problem in the productivity of comb bread production. The results of the analysis of the causes of problems in criterion 2 with the fishbone diagram show that there are differences in labour capabilities and lack of coordination, irregular raw material stocks, limited work areas, no routine maintenance schedule and insufficient oven capacity, the bread cutting process is still manual and documentation regarding raw material stocks is not consistent. Keywords: Fishbone Diagram, Objective Matrix, Productivity